Copper: Synthesis Techniques in Nanoscale and Powerful Application as an Antimicrobial Agent. (8th December 2015) - Camacho-Flores, B. A.; Martínez-Álvarez, O.; Arenas-Arrocena, M. C.; Garcia-Contreras, R.; Argueta-Figueroa, L.; de la Fuente-Hernández, J.; Acosta-Torres, L. S.
Abstract : Nanosized metal particles show specific physical and chemical properties that allow the creation of new composites materials, which are important for multiple applications in biology and medicine such as infections control. Metal nanoparticles, mainly copper, exhibit excellent inhibitory effect on Gram-positive and Gram-negative bacteria; therefore the exploration about the efficient, economical, and friendly environmental technics to synthesize inorganic nanoparticles is imperative. In this work a brief overview of the several methods is made including the comparison of the methods, mainly between sonochemical, microwave, and chemical routes. It allows determining the optimal parameters and technical conditions to synthesize copper nanoparticles with physical and chemical properties suitable for the oral bacterial inhibition.